PERENCANAAN MANAJEMEN KONSTRUKSI PADA PEMBANGUNAN GEDUNG ASRAMA LEMBAGA PENJAMINAN MUTU PENDIDIKAN PROVINSI KALIMANTAN BARAT: PERENCANAAN MANAJEMEN KONSTRUKSI PADA PEMBANGUNAN GEDUNG ASRAMA LEMBAGA PENJAMINAN MUTU PENDIDIKAN PROVINSI KALIMANTAN BARAT - dewi nuryadin, rizka rusmin evita; Agus, watini (RETENSI, 2021)
Project management is an important factor in the implementation of a project, which will affect the cost, timeand quality. Problems that result in interrelated planning, scheduling, control and are the main requirements forevery project success, in these problems there will be many influencing factors, to achieve maximum results in abuilding construction project, a mechanism is needed that can increase the efficiency and effectiveness ofproject management. of available resources. This can be realized through a management planning system thatmeets the criteria for cost (budget), time (quality), human resources (labor), and a field work safety system. The method used in this management plan is to compare the analysis of the labor unit using the SNI method andthe BOW method, and to obtain a budget plan for both methods. In time management, namely counting thenumber of jobs in each item, making the Critical Path Method (CPM), making bar charts, and making S curves,aspects of human resource management are calculating the number of workers on each work item, Occupationalsafety and health management is knowing the hazards and work control health, knowing personal protectiveequipment and knowing work protective equipment.Based on the SNI method, the Cost Budget Plan (RAB) is Rp. 6,300,380,000.00 and based on the BOW methodof the Budget Plan, the amount of Rp. 9,745,770,000.00, with a Plan time of 120 days or 17 weeks.